Die integrasie van gerasde subjektiwiteite binne die konteks van 'n voorgraadse dameskoshuis aan 'n hoëronderwysinstelling: 'n Deleuze/Guattariaanse perspektief - Dick, Liezl (University of the Free State, 2016)
This study focuses on racial integration in an undergraduate women's residence at a higher education institution. The radically unique concepts of Gilles Deleuze and Felix Guattari, with particular focus on their concept of subjectivity, are used to create a different perspective on racial integration. Their concept of subjectivity is used as an alternative to the rational centred Cartesian subject, where identity and rational thought are prioritised. The argument is made that subjectivity is a side effect of a process of connecting and becoming. By proceeding diagnostically, the process of subjectivity can help us understand how subjectivities become racialized and how racism operates. Deleuze/Guattari contribute towards a positive understanding of difference, arguing that no subjectivity can ever really be fixed and static. Race is consequently not perceived as an essential attribute, but rather as a viscous collection of material and immaterial components that stick to certain phenotypes. Subjectivities are territories that become territorialized or deterritorialized; subsequently, racialized subjectivities can become undone to a greater or lesser extent. In this study the conceptual toolbox of Deleuze/Guattari is unpacked. Concepts such as assemblage, the rhizome, molar and molecular, affect, deterritorialization and becoming are discussed. These concepts enable us to move from linear and arboreal thinking, qualities that Deleuze associates with the traditional image of thought of philosophy. An alternative image of thought in the form of the rhizome is proposed which enables thinking to be conceptualised as non-linear and concerned with flow, flux, and connections. A rhizomatic way of thinking is becoming and the reader’s attention is focused on becoming rather than being. In the second part of this study the concepts of Deleuze/Guattari are plugged into the empirical materials that consist of transcripts of conversations, newspaper articles and journal entries. Concepts such as lines of flight, deterritorialization, assemblage and rhizome are connected with the voices of students who live in Madelief residence. The operationalisation of these concepts creates alternative ways of observation, enabling us to understand racial integration differently. These sections of the study form a rhizome and an assemblage – becoming happens when connections are made. The plugging-in of the concepts and empirical materials demonstrates how racialised subjectivities fluctuate between territorialization and deterritorialization. The territorialization of racialized subjectivities via language (order words) and race-habits are demonstrated. The materiality of race is highlighted by indicating that certain material and immaterial components stick to certain phenotypes. This study contributes to a different understanding of race and racialized subjectivities, as well as an alternative perspective on racial integration.

Hierdie studie fokus op rasse-integrasie in ŉ voorgraadse dameskoshuis aan ŉ hoëronderwysinstelling. Gilles Deleuze en Felix Guattari se andersoortige konsepte en denke, met ’n spesifieke fokus op hul andersoortige subjektiwiteitsbeskouing, word gebruik om na rasse-integrasie te kyk. Hulle andersoortige subjektiwiteitsbekouing word dus gebruik as ŉ alternatief vir die rasionele, gesentreerde Kartesiaanse subjek waar identiteit en rasionele denke vooropgestel word. Die argument word gemaak dat subjektiwiteit, as ŉ newe-effek van ŉ proses van koppeling en wording, kan help om op ŉ diagnostiese wyse te verstaan hoe subjektiwiteite geras word, en hoe ras(sisme) werk en gebeur. Deleuze/Guattari wil die positiwiteit van verskil aandui en voer aan dat geen subjektiwiteit werklik vas en staties is nie. Ras word dus nie as iets essensieel beskou nie, maar as ŉ klewerige versameling van materiële en nie-materiële komponente wat kleef aan sekere fenotipes. Subjektiwiteite is terreine wat geterritorialiseer of gedeterritorialiseer word, wat impliseer dat ŉ gerasde subjektiwiteit tot ŉ mindere of meerdere mate ongedaan gemaak kan word. In hierdie studie word Deleuze/Guattari se konsepsuele gereedskapkis uitgepak. Konsepte soos assemblage, die risoom, molêre en molekulêre, affek, deterritorialisering en wording word uiteengesit. Met behulp van hierdie konsepte word daar wegbeweeg van liniêre, boomagtige denke – eienskappe wat Deleuze met die tradisionele denkbeeld van filosofie assosieer. ŉ Alternatiewe denkbeeld in die vorm van die risoom word voorgestel wat ons in staat stel om koppeling, stroming en die nie-liniêre te bedink. ŉ Risoomagtige denkwyse is wording en fokus die leser se aandag op wording eerder as op bestaan. In die tweede gedeelte van hierdie studie word Deleuze/Guattari se konsepte gekoppel met empiriese gegewens wat bestaan uit transkripsies van gesprekke, asook koerantberigte en joernaalinskrywings. Konsepte soos vluglyne, deterritorialisering, assemblage en risoom word gekoppel met die stemme van studente wat in Madelief-koshuis woon. Deur middel van die operasionalisering van hul konsepte, word alternatiewe waarnemingswyses blootgelê om rasse-integrasie anders te verstaan. Hierdie gedeelte van die studie vorm dan ŉ risoom en ŉ assemblage – wording vind plaas weens die koppeling. Die koppeling tussen die konsepte en empiriese gegewens dui aan hoe die gerasde subjektiwiteite tussen territorialisering en deterritorialisering fluktueer. Die wyse waarop gerasde subjektiwiteite geterritorialiseer word, word deur middel van taal (ordeningswoorde) en ras-gewoontes uitgewys. Die materialiteit van ras word aangedui deur te suggereer dat sekere materiële en onstoflike dinge aan sekere fenotipes kleef. Hierdie studie lewer dus ŉ bydrae tot ŉ ander verstaan van ras en gerasde subjektiwiteite; dus ŉ ander verstaan van rasse-integrasie.
Thesis (Ph.D. (School of Higher Education Studies))--University of the Free State, 2016
Keywords: Race discrimination -- South Africa; Multicultural education -- South Africa; Cultural pluralism -- South Africa; Education, Higher -- South Africa